Genotypic Variability and Correlation Studies in Pod and Seed Characteristics of Pongamia pinnata (L.) Pierre in Orissa, India - Deebe Prasad Sahoo; Gyana Ranjan Rout; Swarnalata Das; Subhashree Aparajita; A. K. Mahapatra (International Journal of Forestry Research)
Pongamia pinnata (L.) Pierre is a fast growing leguminous tree with high potential for oil seed production. Fifty-three candidate plus trees (CPTs) of Pongamia pinnata were selected from different locations in Orissa, India, on the basis of their seed and pod characteristics to identify suitable seed source with high oil content for production of quality planting seedling for use in afforestation programs. All the CPTs showed significant variation among themselves in respect to their pod and seed characters. Phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) estimates were high for pod thickness, seed thickness, 100-pod weight, and 100-seed weight. High heritability values accompanied by high genetic advance for 100-seed weight (96.1%, 59.6) and 100-pod weight (90.9%, 37.3) indicated additive gene action. High estimates of genotypic correlations than the corresponding phenotypic correlations indicated the presence of strong inherent association between pod length and pod breadth; 100-pod weight, and pod thickness; 100-pod weight and seed length; 100-seed weight and 100-pod weight. Seed length, seed breadth, seed thickness, 100-pod weight and 100-seed weight had significant positive correlation with each other, and these characters should be considered as effective parameters to select CPTs for different agroforestry programs.